Synthesis and Characterization of Magnetite/Gold Core Shell Nanoparticles Stabilized with a β-cyclodextrin Nanosponge to Develop a Magneto-Plasmonic System - Silva-Gonzalez, N; Silva-Gonzalez, N; Araneda, F; Salazar-Sandoval, S (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Magnetite/gold core-shell nanoparticles (magnetite/gold NPs) have important optical and magnetic properties that provide potential for applications, especially biomedical ones. However, their preparation is not exempt from difficulties that might lead to unexpected or undesired structures. This work reports the synthesis and characterization of magnetite/gold NPs using tetramethylammonium hydroxide (TMAH) to promote the formation of a continuous interface between the magnetite core and the thin gold shell. The synthesized magnetite/gold NPs were characterized using transmission electron microscopy (TEM), energy-dispersive spectroscopy (EDS), field emission scanning electron microscope (FE-SEM), ζ-potential, vibrating sample magnetometer (VSM), selected area electron diffraction (SAED), UV-Visible spectroscopy, and dynamic light scattering (DLS), confirming the core-shell structure of the NPs with narrow size distribution while evidencing its plasmonic and superparamagnetic properties as well. Further, the magnetite/gold NPs were associated and stabilized with a β-cyclodextrin nanosponge (β-CDNSs), obtaining a versatile magneto-plasmonic system for potential applications in the encapsulation and controlled release of drugs. © 2023 by the authors.